On the equivalence of Bayesian and dominant strategy implementation: The case of non-linear utilities - Alexey Kushnir; Shuo Liu (University of Zurich, Department of Economics, 2015)
We extend the equivalence between Bayesian and dominant strategy implementation established by Gershkov et al. (Econometrica, 2013) to environments with non-linear utilities satisfying the average single-crossing property and the convex-valued assumption. The new equivalence result produces novel implications to the literature on the principal-agent problem with allocative externalities, environmental mechanism design, and public good provision.
Keywords: D82; 330; Bayesian implementation; dominant strategy implementation; mechanism design; non-linear utilities; single-crossing